Formation and growth of stacking fault tetrahedra in Ni via vacancy aggregation mechanism. (15th March 2016) - Aidhy, Dilpuneet S.; Lu, Chenyang; Jin, Ke; Bei, Hongbin; Zhang, Yanwen; Wang, Lumin; Weber, William J.
Abstract: Using molecular dynamics simulations, the formation and growth of stacking fault tetrahedra (SFT) are captured by vacancy cluster diffusion and aggregation mechanisms in Ni. The vacancy-tetrahedron acts as a nucleation point for SFT formation. Simulations show that perfect SFT can grow to the next size perfect SFT via a vacancy aggregation mechanism. The stopping and range of ions in matter (SRIM) calculations and transmission electron microscopy (TEM) observations reveal that SFT can form farther away from the initial cascade-event locations, indicating the operation of diffusion-based vacancy-aggregation mechanism. Graphical abstract: